The reality of applying Bologna process in education from the students of Zakho University viewpoint - Shoukry, Bewar; Mohammed , Mohammed; Haji, Star (Humanities Journal of University of Zakho, 2023)
The current study aimed to identify the viewpoint of the students of University of Zakho about the reality of applying Bologna process in university education, and the significance of the differences in their viewpoints according to the demographic variables: gender, class, and specialization. The sample consisted of (750) male and female students who were chosen in a stratified random manner from the colleges and faculties of University of Zakho. To achieve the objectives of the study, the researchers prepared a questionnaire consisting of (41) items divided into four dimensions. The study’s validity and reliability indicators were verified. The data were treated statistically using the arithmetic means and standard deviations, in addition to using the t-test for one sample and for two independent samples. The results indicated that the reality of applying Bologna Process from the students’ point of view is good or high. Besides, there was a significant difference in the students’ point of view about the reality of applying Bologna Process due to the college variable and in favor of the humanities colleges. No significant differences appeared in their views according to gender and class. In light of the results, a set of recommendations and proposals were presented.